Memahami Komunikasi Antar Pribadi Dalam Pernikahan Beda Agama Dalam Upaya Mempertahankan Hubungan Yang Harmonis. - Indahyani, Indahyani (Jurnal The Messenger, 2013)
Interfaith marriage is a form of marriage is performed by a pair of men and women who have different religious beliefs. Currently interfaith marriage is already banned by the government and the logic, in the se-religious marriages can be conflict and does not guarantee a successful marriage, let alone a different religion. Although conflict in marriage is not only caused by differences in belief, but it is very influential for the survival of marriage as the basis of different faiths will make all the difference. Although it is not easy to maintain interfaith marriage, but not a few marriages that last a long time despite the different religions. Effective communication will minimize the occurrence of conflict, so the marriage will last a long time. This study seeks to examine more deeply the Self Disclosure (Self Disclosure) In Johari Window Theory, Theory of Dialectical relations (Relational Dialectics), and symbolic interactionism (symbolic Interactionism). Further in-depth interviews with select speakers who have certain criteria as research subjects, by using descriptive qualitative research methods. Presentation of data is done as it is delivered in accordance informants as research subjects without manipulation. Then, the researchers interpret the data to describe the phenomenon that occurs in study subjects.